Autophagy at the interface of endothelial cell homeostasis and vascular disease. (2nd May 2021) - Mameli, Eleonora; Martello, Andrea; Caporali, Andrea
Abstract : Autophagy is an essential intracellular process for cellular quality control. It enables cell homeostasis through the selective degradation of harmful protein aggregates and damaged organelles. Autophagy is essential for recycling nutrients, generating energy to maintain cell viability in most tissues and during adverse conditions such as hypoxia/ischaemia. The progressive understanding of the mechanisms modulating autophagy in the vasculature has recently led numerous studies to link intact autophagic responses with endothelial cell (EC) homeostasis and function. Preserved autophagic flux within the ECs has an essential role in maintaining their physiological characteristics, whereas defective autophagy can promote endothelial pro‐inflammatory and atherogenic phenotype. However, we still lack a good knowledge of the complete molecular repertoire controlling various aspects of endothelial autophagy and how this is associated with vascular diseases. Here, we provide an overview of the current state of the art of autophagy in ECs. We review the discoveries that have so far defined autophagy as an essential mechanism in vascular biology and analyse how autophagy influences ECs behaviour in vascular disease. Finally, we emphasise opportunities for compounds to regulate autophagy in ECs and discuss the challenges of exploiting them to resolve vascular disease. Abstract : Autophagy is the intracellular process that allows the selective degradation of damaged organelles, harmful protein aggregates and the recycling of cellular components. The autophagic process plays a fundamental role in maintaining endothelial cells (EC) homeostasis. This review discusses the most recent findings that clarify autophagy involvement in vascular biology and how it influences ECs dysfunction in vascular disease.